Ethno-iconographic Vogue’s editorials (1948-2016): an approach to cultural diplomacies - Llorente Villasevil, Ana; Díaz Soloaga, Paloma (RIHC. Revista Internacional de Historia de la Comunicación, 2018)
This article offers an overview of a seminal research that has laid its foundations in a systematization of the messages emerging from the interface between different cultures through fashion communication and image making. It delves into a semantic study on the variety of compositions related to ethno-iconography that have been developed by western editions of Vogue since 1948. In parallel, it examines the continuity of their visual discourses by recent non-western editions. It explores the relation between the functions of the fashion magazines per se, and those of the travel magazines, ethnographic photography and even documentary photojournalism. From this interpretative framework, the study assess the potential of fashion magazine as an instrument that provides visibility to social realities and that acts as triggers of critical reflection and agents capable of establishing inter-cultural relations.